Spatiotemporal reconstruction and drivers of tourism-oriented towns: A case study of Jinshitan - Song, Chunrui; Yang, Jun; Wang, Ling-en; Li, Yutong; Zhi, Yin; Xia, Jianhong (Cecilia) (Frontiers in Environmental Science, 2022)
Reconstruction of settlement spaces is the process of optimizing and reorganizing the internal resources of a settlement, which is of great significance to settlement development. In this study, we used the land-use transfer matrix, land-use dynamics, building density, mean building height, and plot ratio in four time series to explore the 2-dimensional and 3-dimensional space, production space reconstruction and its drivers. The conclusions were as follows: (1) 82.288 % of cultivated land that was lost during the study period was transformed as construction land, which was concentrated in patches; (2) showed a high degree of consistency in terms of building density, mean building height, and floor area ratio; (3) domestic tourists accounted for the majority of tourism, and the population structure exhibited a non-agricultural transformation; and (4) the spatial reconstruction of Jinshitan has benefited from natural resource endowment, government policy guidance, market orientation, and participation of social subjects.